A Comparative Study of Women Empowerment among Rural and Urban Female Secondary School Teachers in Punjab State (British Journal of Multidisciplinary and Advanced Studies, 2024)
Teacher empowerment means a teacher who has the power of taking decisions, opportunities to get knowledge and professional growth, and also have the recognition and autonomous power. The present research designed to study and compare the women empowerment of female secondary school teachers. The descriptive survey research method was used for the present study. A representative sample of 500 (250 rural and 250 urban) female secondary school teachers selected randomly from twenty (10 rural and 10 urban) randomly selected school from five randomly selected districts of Punjab. A self-constructed tool in the form of scale using Likert method of scale construction for measuring empowerment of female secondary school teacher. Mean, S.D. and t- test were used to draw the conclusions. Finding of the study shows that no significant difference was found between rural and urban female secondary school teachers on women empowerment.